Spectral efficiency maximisation of full‐duplex enabled relaying SWIPT system with successive interference cancellation and maximal ratio combining. Issue 12 (1st July 2020) - Peng, Xuefei; Li, Jiandong
Abstract : In this study, the authors propose a spectral efficiency maximisation problem in power splitting (PS)‐based relaying simultaneous wireless information and power transfer (SWIPT) system with full‐duplex (FD) decode‐and‐forward (DF) ability considering the presence of a direct link. Firstly, the authors establish the system model for PS‐based relaying SWIPT system with FD DF ability considering the presence of a direct link. Secondly, they propose an information decoding scheme considering successive interference cancellation and maximal ratio combining techniques. Further, they formulate the spectral efficiency maximisation problem based on the established system. Then, the formulated problem is solved through the proposed iterative PS ratio algorithm, where the designed information scheme is applied. Finally, the better performance of the proposed scheme is demonstrated through a number of simulations.